Communicating unexpected news to pregnant people living with mental health conditions in fetal medicine (the UNDERSTAND study): Healthcare professionals’ perspectives - Ioannis Karapanos; Iona Hindes; Jemima Dooley; Nikolina Jovanović; Maddalena Miele; Jane Fisher; Stamatina Iliodromiti; Elena Greco (PLoS ONE, 2026)
Objectives This study explores the perspectives and experiences of healthcare professionals (HCPs) in a multidisciplinary fetal medicine (FM) team when delivering unexpected news in fetal medicine, with a particular focus on pregnant people living with mental health conditions (MHCs). It aims to identify communication strategies and highlight facilitators and barriers to effective consultations in these challenging situations. Methods Qualitative study involving 20 semi-structured interviews with HCPs from multi-disciplinary FM teams in a large NHS Trust in East London. Participants included FM specialists, neonatologists, midwives, and specialist nurses. Data were analyzed using reflexive thematic analysis to identify key themes representing participants’ perspectives. Results Five key themes emerged: (1) enhancing patient understanding, (2) supporting patients (3) individualizing care, (4) supporting HCPs and (5) the impact of health inequalities in FM. Facilitators of effective communication included optimizing the setting, avoiding ambiguity, fostering understanding, and involving significant others in discussions. Barriers included language limitations, where reliance on interpreters hindered effective and compassionate communication, and poor pregnancy-related health literacy, particularly in socio-economically deprived populations, which impeded informed decision-making. Clinician-related barriers included reluctance to address MHC due to lack of training, stigma around mental health, and time constraints. The emotional toll of frequently delivering distressing news was identified as a significant challenge for HCPs, yet formal support mechanisms were lacking. Conclusion HCPs in FM emphasized that delivering unexpected news requires a patient-centred approach that considers individual needs, is culturally sensitive, and addresses language and health literacy barriers. The mental health and well-being of both those receiving and delivering the news remains largely overlooked. Currently, no specific communication training exists for HCPs in FM and limited or no support is available for individuals with mild, pre-existing, or suspected MHC, despite their prevalence and the recognition that difficult news during pregnancy may exacerbate these conditions. Future research should evaluate communication frameworks co-produced by HCPs and individuals with lived experience to improve FM consultations for patients with and without MHC. Enhanced mental health support is urgently needed for both patients and HCPs in FM.